Understanding of mental fatigue in elite fencing sports: perspectives from Chinese national level fencers - Bian, Chao; Russell, Suzanna; De Pauw, Kevin; Habay, Jelle; Bogataj, Špela; Roelands, Bart (Frontiers in Psychology, 2025)
IntroductionRecent studies have documented the presence, fluctuation, and persistence of mental fatigue (MF) across various elite sports. It appears that open-skilled competitive contexts tend to impose greater mental demands, leading to higher levels of MF. Fencing, as an open-skilled combat sport, requires perceptual-cognitive skills and mental resources allocation for an optimal performance. However, it is underrepresented in the MF research domain.MethodsThis study employed a cross-sectional design using an online survey to capture Tier 3–5 Chinese fencers’ perceptions of MF and their general understanding of the contributors that may induce MF in fencing. Descriptive reports, thematic analysis, comparisons of retrospective MF perceptions (MVAS) and different contributors to MF inducement in training and competition were conducted.ResultsThe results highlight a contextual difference of MF (training vs. competition), and the contributions of timing-related decision-making moments and execution of offensive actions to the MF inducement in fencing. Furthermore, MF was perceived higher in the direct elimination stage competition than in the pool stage (MVAS: 57.6 ± 21.0 vs. 49.2 ± 21.7 AU). Individuals’ health conditions and competition-oriented elements were rated as synergistic factors of MF perception, while external commitments were rated lower.DiscussionThese findings emphasize the presence of MF in fencers and encourage researchers and practitioners to assess and deliberately manage MF. Future studies should involve longitudinal, multifactor observations on diverse fencers and contexts to validate current findings, with a focus on specific in-match scenarios to enhance the representativeness and inform targeted training and management strategies for MF in fencing.